5th International Conference on Higher Education Advances (HEAd'19) 2019
DOI: 10.4995/head19.2019.9250
|View full text |Cite
|
Sign up to set email alerts
|

Whiteboard Animations for Flipped Classrooms in a Common Core Science General Education Course

Abstract: Whiteboard animation, an engaging tool for teaching and learning, consists of a series of hand-drawing illustrations with voice-over narration to explain complex and abstract ideas. Our team had produced four short whiteboard animations tailor-made for a common core science general education (GE) course. This study aims at evaluating the effectiveness of using these whiteboard animations for flipped classrooms in the common core science GE course. The pre-tutorial survey showed that students who watched the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 2 publications
2
14
0
2
Order By: Relevance
“…Although recent studies into the creation of whiteboard animations are interesting, Türkay (2016) argues that learner interactions with this form of animation are not appropriately understood. Li et al (2019) noted that whiteboard animation, an enticing learning device, consists of a series of manual images with voice-over storytelling that convey complex and abstract concepts. From their research, it was concluded that the whiteboard animation is a powerful and stimulating resource for fluent teaching in the GE (General Education) course.…”
Section: Whiteboard Animationmentioning
confidence: 99%
See 1 more Smart Citation
“…Although recent studies into the creation of whiteboard animations are interesting, Türkay (2016) argues that learner interactions with this form of animation are not appropriately understood. Li et al (2019) noted that whiteboard animation, an enticing learning device, consists of a series of manual images with voice-over storytelling that convey complex and abstract concepts. From their research, it was concluded that the whiteboard animation is a powerful and stimulating resource for fluent teaching in the GE (General Education) course.…”
Section: Whiteboard Animationmentioning
confidence: 99%
“…Then, Karthigesu & Mohamad (2020) have shown that by engaging whiteboard integration allows teachers to modify their software to make learning a language more enjoyable, engaging and energetic. Furthermore, based on the students' perception on the research conducted by Li et al (2019), the contents of whiteboard animation are interesting, animated and allowing the students to understand the details.…”
Section: The Difference In Students' English Presentation Skills Taugmentioning
confidence: 99%
“…Learning by using video can provide independent learning solutions because it is not obstructed by distance and time [15]. Whiteboard animation videos can be used as a means of conveying the material [16]. Animation in a video can visualize the application or depiction of a material.…”
Section: Introductionmentioning
confidence: 99%
“…In the production stage, performed with the recording process itself, the information from the previous stage was inserted into the Video Scribe platform, in the Whiteboard animation format, which contains ready-made illustrations in its collection, as well as it allows Internet searches for images not available 11 . For proper acoustics, the video's audio was recorded in Studio Apollo 17.…”
Section: Methodsmentioning
confidence: 99%